In vitro assessment of primary human chondrocyte viability following treatment with intra-articular contrast agents and local anaesthetic - Broderick, James Michael (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2021)
Title In vitro assessment of primary human chondrocyte viability following treatment with intra-articular contrast agents and local anaesthetic. Introduction Magnetic resonance (MR) and computed tomography (CT) direct arthrography, procedures in which either gadolinium or iodine-based contrast agents are administered intra-articularly, are commonly used tools in musculoskeletal diagnosis. Although considered safe for systemic use, toxicities have been identified for these agents in some tissues, yet, there have been few studies examining their toxicity on the joint. The aims of this study were to (i) investigate the effect of four routinely used intra-articular contrast agents on primary human chondrocyte viability in both a time-dependent and dose-dependent fashion, and (ii) determine the additive effect of local anaesthetic to the contrast media. Methods Primary human chondrocytes, isolated from 34 femoral heads obtained at the time of bipolar hemiarthroplasty for femoral neck fracture, were grown in monolayer culture. Chondrocyte phenotype was confirmed with Collagen II expression. In one set of experiments, chondrocytes were exposed to each contrast agent in isolation (Iohexol 50, 100, 200 mg/ml; Iopromide 50, 100, 200 mg/ml; Gadopentetate Dimeglumine 1.7, 2.5, 5, 10 mmol/L; Gadobenate Dimeglumine 1.7, 2.5, 5, 10 mmol/L) for 1, 4, 16 or 24 hours. Each agent was in solution with cell culture media. In a second set of experiments, chondrocytes were exposed to a clinical injection ?cocktail? (Iohexol 150 mg/ml; Gadopentetate Dimeglumine 2.5 mmol/L; Lidocaine 0.5%; Lidocaine 1%; Iohexol + Lidocaine (final concentrations of 150 mg/ml and 0.5%, respectively); Gadopentetate Dimeglumine + Lidocaine (final concentrations of 2.5 mmol/L and 0.5%, respectively) for 30, 45 and 60 minutes. Cells exposed to cell culture media or saline served as controls. Twenty-four hours after exposure, cell viability was assessed using the Cell-Titer 96? AQueous One Solution Cell Proliferation Assay and crystal violet staining. Results Gadolinium-based contrast agents did not cause a significant decrease in chondrocyte viability in either a time-dependent or dose-dependent fashion. At 1 and 4 hours, iodine-based contrast agents did not cause a decrease in chondrocyte viability at any concentration. At 16 hours, a significant reduction in cell viability was noted at both 100 mg/ml and 200 mg/ml in the Iohexol-treated group and at 200 mg/ml in the Iopromide-treated group. At 24 hours, no decrease in cell viability was noted at any concentration in the Iohexol-treated group, but cell viability was reduced at 100 mg/ml and 200 mg/ml in the Iopromide-treated group. Exposure of primary human chondrocytes to any concentration of lidocaine - either in isolation or in solution with Iohexol or Gadopentetate Dimeglumine - led to a profound decrease in cell viability at each time point. Conclusion Gadolinium-based contrast agents are safe for intra-articular injection at the concentrations routinely used in clinical practice. While prolonged exposure to higher doses of iodine-based contrast agents led to a decrease in cell viability in comparison to a media control, no evidence of time-dependent effects were observed at a concentration of either 50 mg/ml or 200 mg/ml. However, the addition of lidocaine to both MR and CT arthrogram solutions caused a significant decrease in cell viability, which occurred in both a time-dependent and dose-dependent fashion. These in vitro findings suggest that local anaesthetics should not be routinely added to intra-articular radiographic contrast agents.
APPROVED
Keywords: Arthrography; Intra-Articular Contrast; Chondrotoxicity; Local Anaesthetic; Cartilage